Religious Memetics: Institutional Authority in Digital/Lived Religion. (October 2015) - Burroughs, Benjamin; Feller, Gavin
Recently leaders of the Church of Jesus Christ of Latter-day Saints (LDS/Mormon) faith have called upon members to "sweep the earth" with positive religious messages through social media. This digital moment in Mormonism exemplifies the interrelation and concomitant tension between everyday lived religion, technology, and religious institutions. While studies on digital religion have emphasized the push of participatory culture into everyday lived religion, this research on religious memes contributes to an emergent vein of digital religion scholarship focused on institutional authority. In our analysis of the "doubt your doubts" meme and antimemes we theorize religious memetics as a space for the reconnection of the everydayness of religious practice, which boils down meaningful moments of faith into facile, nonthreatening avenues for sharing religion. While this is beneficial for institutions, the reflexive and metonymic function of religious memes ruptures routine, offering participants momentary pauses from the demands of orthodox religious life.